2000
DOI: 10.3171/spi.2000.92.2.0169
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of blood parameters following anterior cervical fusion

Abstract: Object. Both C-reactive protein (CRP) level and erythrocyte sedimentation rate (ESR) were measured prospectively in 51 cases in which uncomplicated cervical anterior fusion was performed. The object of the authors was to quantify the differences in the responses of these parameters recorded in the immediate postoperative period and to determine factors influencing their course. Methods. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
6
1
1
Order By: Relevance
“…Previous studies have reported that the predisposing factors for bacterial spondylitis or psoas abscesses were diabetes mellitus, malnutrition, substance abuse, human immunodeficiency virus infection, malignancy, long-term steroid use, chronic renal failure, liver cirrhosis, and sepsis [ 4 8 ]. Some reports have showed that CRP or WBCs were associated with recovery [ 9 , 10 ], although our study showed that CRP was also associated with gram-negative rods.…”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies have reported that the predisposing factors for bacterial spondylitis or psoas abscesses were diabetes mellitus, malnutrition, substance abuse, human immunodeficiency virus infection, malignancy, long-term steroid use, chronic renal failure, liver cirrhosis, and sepsis [ 4 8 ]. Some reports have showed that CRP or WBCs were associated with recovery [ 9 , 10 ], although our study showed that CRP was also associated with gram-negative rods.…”
Section: Discussioncontrasting
confidence: 80%
“…However, we could not find a connection between high postoperative ESR levels and the presence of a SSI. In concordance of our study, it was reported in the literature that CRP was more sensitive and specific than ESR when evaluating the response to the treatment of infection (27)(28)(29).…”
Section: Biochemical and Microbiological Investigationssupporting
confidence: 80%
“…Although CRP and ESR are elevated after spinal surgery or infections, CRP normalises postoperatively or after appropriate treatment of an infectious process faster than the ESR. Rosahl et al [27] showed that ESR remained markedly elevated ten days after anterior cervical discectomy and fusion with a peak on postoperative day three whereas the CRP returned to less than 50% of its peak level by postoperative day five. Therefore an elevation in CRP and/or ESR should not be taken as pathognomonic for an infection; however, these both serve as good screening and surveillance tests in the diagnosis and treatment of spinal infections.…”
Section: Laboratory Testsmentioning
confidence: 99%